2020
DOI: 10.1016/j.jaad.2019.07.074
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab shows long-term safety and efficacy in patients with moderate to severe atopic dermatitis enrolled in a phase 3 open-label extension study

Abstract: is a principal investigator and advisory board member for AbbVie; is an advisory board member for Eli Lilly; is a principal investigator for LEO Pharma; is a principal investigator and advisory board member for Pfizer; is a principal investigator, provides research support, has received honoraria for lecturing, and is an advisory board member and consultant for Regeneron Pharmaceuticals and Sanofi Genzyme; and is an advisory board member for UCB. Dr Blauvelt is a scientific advisor and clinical study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
167
4
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(195 citation statements)
references
References 40 publications
(72 reference statements)
13
167
4
11
Order By: Relevance
“…Dupilumab is a fully humanized monoclonal antibody targeting the interleukin‐4 receptor alpha (IL‐4Rα), a receptor subunit shared by two type 2 cytokines, IL‐4 and IL‐13, which play an important role in the pathogenesis of atopic dermatitis. Besides being an effective treatment for atopic dermatitis, dupilumab has been shown to be effective for the treatment of generalized pruritus and prurigo nodularis in several recent reports, suggesting that it may possibly benefit patients with EBP.…”
mentioning
confidence: 99%
“…Dupilumab is a fully humanized monoclonal antibody targeting the interleukin‐4 receptor alpha (IL‐4Rα), a receptor subunit shared by two type 2 cytokines, IL‐4 and IL‐13, which play an important role in the pathogenesis of atopic dermatitis. Besides being an effective treatment for atopic dermatitis, dupilumab has been shown to be effective for the treatment of generalized pruritus and prurigo nodularis in several recent reports, suggesting that it may possibly benefit patients with EBP.…”
mentioning
confidence: 99%
“…Therefore, possibly other cytokine profiles result into palmar hyperkeratosis in HHE. 40,41,48,50,53 Hereditary PPK is another group of skin diseases with palmar hyperkeratosis, which provides more insight about the association of different keratins, desmosomal proteins and epidermal barrier proteins to palmoplantar hyperkeratosis. [8][9][10][54][55][56][57][58] In this study no monogenetic mutations related to palmar hyperkeratosis were found.…”
Section: Discussionmentioning
confidence: 99%
“…Alitretinoin was studied in large randomized controlled trials with more than 1600 participants and showed positive effects on all hand eczema subtypes. [51][52][53] Treatment with 30 mg/day of alitretinoin resulted in clear or almost clear hand eczema in 48% of the participants, compared Vesicular eruptions on the palms and/or sides of the fingers. Eruptions may occur at intervals of weeks of months and may be so frequent that a chronic eczema is seen.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations